Taxonomic review of the Neotropical genus Gephyrocharax Eigenmann, 1912 (Characiformes, Characidae, Stevardiinae) - Vanegas-Ríos, James A. (Zootaxa, 2016)
Gephyrocharax currently comprises 13 valid species distributed in the Cis- and Trans-Andean basins of the Neotropical region. The genus has not been reviewed in more than 80 years, and thus, the older species descriptions are poorly detailed, based on small samples of specimens, and supported by uninformative diagnoses. The present review is based on external morphology and morphometric, meristic, osteological, and myological data. Counts and measurements were analyzed using bivariate and multivariate statistical procedures implemented in PAST and SigmaPlot. Cases of synonyms and geographic variation were evaluated using sheared principal components analyses (SPCA). Eleven valid species are recognized for the genus: G. atracaudatus, G. caucanus, G. chocoensis, G. intermedius, G. major, G. martae, G. melanocheir, G. sinuensis, G. torresi, G. valencia, and G. venezuelae. Gephyrocharax whaleri is proposed as junior synonym of G. intermedius, and Corynopomops opisthopterus and G. chaparae are proposed as junior synonyms of G. major. A lectotype for G. major and neotypes for G. melanocheir and G. sinuensis are designated. Gephyrocharax atracaudatus is confirmed for the first time in the Palenque River basin of the Pears islands in the Gulf of Panama. New distributional records are reported for G. major in the Amazon River basin. Gephyrocharax major and G. valencia are the most widely distributed members of the genus. Distributional and georeferenced maps are presented for all Gephyrocharax species based on extensive examined material. An identification key of the Gephyrocharax species is provided.